2013
DOI: 10.11606/rco.v7i18.55429
|View full text |Cite
|
Sign up to set email alerts
|

Escolha De Práticas Contábeis: Um Estudo Sobre Propriedades Para Investimento Em Empresas Brasileiras Não Financeiras De Capital Aberto

Abstract: <p>O objetivo do artigo foi analisar os incentivos econômicos para seleção do método (custo ou valor justo) de mensuração contábil das propriedades para investimento por parte das empresas brasileiras não financeiras de capital aberto. Foi realizada uma análise quantitativa através de estatística univariada (teste de diferença de média <em>Mann-Whitney U</em> e teste de proporções) e multivariada (regressão logística) para análise de 36 empresas com propriedades para investimento. Os resultad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 1 publication
2
10
0
23
Order By: Relevance
“…The greater the size of companies from these Latin American countries that compose the sample, the lower their future results will be, as indicated by Cullinan (1999) and also by Costa, Silva and Laurencel (2013). The results for leverage show that higher company debt contributes to market uncertainty, in accordance with prior literature from Ayres et al (2010).…”
Section: Forecasting Modelsupporting
confidence: 85%
“…The greater the size of companies from these Latin American countries that compose the sample, the lower their future results will be, as indicated by Cullinan (1999) and also by Costa, Silva and Laurencel (2013). The results for leverage show that higher company debt contributes to market uncertainty, in accordance with prior literature from Ayres et al (2010).…”
Section: Forecasting Modelsupporting
confidence: 85%
“…The latter claims that, since users have expectations about companies' profitability, managers tend to choose the method that best contribute to achieve the performance desired by investors (fair value). However, with regard to intangible assets and IP, which were not statistically significant, these findings corroborate the results of previous studies (Cole et al, 2011;Andrade et al, 2013;Costa et al, 2013;Souza et al, 2015), which found that profitability does not influence managers' accounting choice to use the historical cost or fair value method.…”
Section: Regression Analysissupporting
confidence: 90%
“…A statistically significant profitability for fixed assets, in turn, had a negative sign (historical cost), contradicting the theory (Costa et al, 2013;Christensen & Nikolaev, 2013). The latter claims that, since users have expectations about companies' profitability, managers tend to choose the method that best contribute to achieve the performance desired by investors (fair value).…”
Section: Regression Analysismentioning
confidence: 91%
See 2 more Smart Citations